Prevalence of soil-transmitted helminth in soil irrigated with wastewater in Sharkia Governorate, Egypt with a reference to the seasonal variation - Al Hoot, Abd Allah A.; Etewa, Samia E.; Arafa, Salwa Z.; Rashad, Suzan I. (Journal of Advanced Veterinary Research, 2024)
The objective of this study was to assess the extent of parasitological contamination of soil irrigated with wastewater. Samples were randomly collected including soil, and water samples from which soils were watered. Samples were taken from different locations in Sharkia governorate, in the east of Nile Delta, Egypt. Such locations were irrigated from water canals, namely El-Ganabia, Sherwida, El-mahmodyia, El-Senety, and Saft Zerek. The samples were collected monthly during September 2021 to September 2022. More than half of the collected samples (60.7%) tested significantly positive for parasite contamination. The largest proportion of pollution was found in areas near the El-Senety Canal with a rate of infection (80%), whereas soil samples near the Moias Canal area had significantly the lowest (40%). 40.8% of positive samples had one parasite species, whereas 37.9% and 11.5% of positive samples were infected with parasites.